Web-Based Cash Management Application Program at PT Perusahaan Perdagangan Indonesia, Banjarmasin Branch - Fitria, Fitria; Iryanie, Emy; Heldalina, Heldalina (Indonesian Journal of Advanced Research, 2024)
With the advancement of technology, the need for an effective and efficient system to manage company funds has become crucial. Meanwhile, at PT Perusahaan Perdagangan Indonesia Banjarmasin Branch, financial records are still not computerized. The author utilized case study and literature review methods for data collection and employed the waterfall method in system development. The research findings indicate that the developed cash management information system can swiftly process large-scale data, providing accurate information as per user requests. This undoubtedly facilitates employees in generating financial reports, thereby enhancing financial management effectiveness and efficiency.